SILK ROAD, ISLAM, AND CONFUCIANISM - Osman Bakar (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2024)
The history of the Silk Road, or Silk Routes as some historians prefer to call it, is one of the most impactful periods in human history spanning nearly sixteen centuries, from the second century BCE until the fifteenth century CE. It was the opening of trade to the outside world by the Han dynasty in China in 130 BCE that opened the official curtain of the Silk Road history. This Silk Road history may be regarded as the history of the encounters of the greatest human civilisations before modern times. It is a period of history that witnessed the birth of two great religions and civilisations of the world, namely Christianity and Islam. In the context of our present discussion, it is not the history of the individual religions and civilisations sharing the approximately 6,437 kilometre or 4,000 milelong Silk Road that mainly interests us. Rather, it is the inter-civilisational encounters that went into the shaping of the Silk Road history in question.